Preparation of legal instruments for Village Owned Enterprises Mitra Cibogo Sejahtera - Taufik Raharjo; Aditya Wirawan (Universitas Muhammadiyah Magelang, 2023)
The purpose of this community service project is to collect documents on the legal framework of the village-owned businesses (BUMDesa) in Cibogo Village. The method used for this act of community service can be separated down into three phases: planning, implementation, and evaluation. Partner interviews and the development of work concepts are both used in planning. The creation of the concept, selection, and socialization of institutional devices are carried out during the implementation stage. The success of the activity is assessed during the evaluation phase. This community service project resulted in a Village Regulation regarding its establishment of BUMDesa. Furthermore, it is also produced BPD decision documents, statutes, bylaws, and decrees regarding the appointment of BUMDesa management.